COVID-19 syndemic in Asia up to 12/03/2021 - Mora-Alvarado, Darner A. (2022)
The present study shows the evolution of COVID-19 health crisis provoked by SARS-CoV-2 in which the first patient was reported in Wuhan, China on November the 17th 2019. Firstly, a comparison of infections and deaths is analysed between the five continents. Asia reported 74 010 689 infections, 1 104 494 deaths, and a mortality rate of 1.55 %. On the other hand, India reported 34 615 757 infections, whereas USA reported 49 718 525 infections. India reported the highest number of deaths relate to COVID-19 with 615 225 followed by Russia with 8 839 981 infections and 278 857 deaths. In short, within the most affected nations by these diseases, we found India, Russia, Turkey, Iran, and Indonesia. On the other hand, vaccination progresses in Asia are very unequal, where Cambodia occupied the first place and Yemen the last one with 1.21 %. Discipline in the application of prevention measures in Asian countries is its greatest strength. Finally, it is paradoxical that China - where the crisis has originated – is currently one of the nations with the fewest cases and deaths in the world.